2008
DOI: 10.1073/pnas.0805319105
|View full text |Cite
|
Sign up to set email alerts
|

Extreme diversity of tropical parasitoid wasps exposed by iterative integration of natural history, DNA barcoding, morphology, and collections

Abstract: We DNA barcoded 2,597 parasitoid wasps belonging to 6 microgastrine braconid genera reared from parapatric tropical dry forest, cloud forest, and rain forest in Area de Conservació n Guanacaste (ACG) in northwestern Costa Rica and combined these data with records of caterpillar hosts and morphological analyses. We asked whether barcoding and morphology discover the same provisional species and whether the biological entities revealed by our analysis are congruent with wasp host specificity. Morphological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
602
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 539 publications
(635 citation statements)
references
References 26 publications
29
602
2
2
Order By: Relevance
“…Recent large-scale DNA barcoding campaigns have demonstrated that DNA barcoding will have to face the undescribed diversity of earth biotas [e.g. [27][28][29] and that DNA barcodes might help to speed up the pace of species discovery through automated delineation of mitochondrial lineages. This approach is particularly relevant when applied to areas of exceptional diversity facing massive anthropogenic threats and as such, urgently awaiting more comprehensive assessments [1][2][3]185].…”
Section: New Tools For Species Identification Environmental Dna Barcmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent large-scale DNA barcoding campaigns have demonstrated that DNA barcoding will have to face the undescribed diversity of earth biotas [e.g. [27][28][29] and that DNA barcodes might help to speed up the pace of species discovery through automated delineation of mitochondrial lineages. This approach is particularly relevant when applied to areas of exceptional diversity facing massive anthropogenic threats and as such, urgently awaiting more comprehensive assessments [1][2][3]185].…”
Section: New Tools For Species Identification Environmental Dna Barcmentioning
confidence: 99%
“…Compared to morphological characters, DNA barcodes presents several advantages: (1) intraspecific phenotypic variation often These detailed specimens and barcode records ensure the reproducibility of the PCR and sequencing protocols by providing contact of the peoples involved in generating DNA barcodes. In addition, it enables the continuous updating of the identification of specimens by the community of users and facilitates the use of DNA barcodes for further taxonomic studies [21,[27][28][29][30][31]183]. To further improve the quality of DNA barcode data, the BARCODE data standard as been implemented in GenBank for the records that are compliant with the following requirements: 1.…”
Section: Dna Barcoding: a Solution To The Taxonomic Impediment?mentioning
confidence: 99%
See 2 more Smart Citations
“…High herbivore host diversity and shared generalist natural enemies can be reconciled if apparent generalist enemies in fact comprise genetically divergent cryptic lineages that each attack only a subset of the species’ recorded host range. Such structuring has been revealed in a range of systems (Forbes, Powell, Stelinski, Smith, & Feder, 2009; Hood et al., 2015; Smith, Wood, Janzen, Hallwachs, & Hebert, 2007; Smith et al., 2008; Stireman et al., 2006). More broadly, understanding how insect herbivores and parasitoid communities are structured has implications for many aspects of ecosystem management, including biological control of herbivorous pests (Carvalheiro, Buckley, Ventim, Fowler, & Memmott, 2008; Henneman & Memmott, 2001), and predicting the impacts of range expansions associated with anthropogenic introductions and climate change (Nicholls, Fuentes‐Utrilla, et al., 2010; Sax et al., 2007).…”
Section: Introductionmentioning
confidence: 99%